Distinguish to Unite, or The Degrees of Knowledge - Maritain, Jacques (Collected Works of Jacques Maritain Ser., 1995)
Maritain argues that there are different 'kinds' and 'orders' of knowledge and, within them, different 'degrees' determined by the nature of the thing to be known and the 'degree of abstraction' involved. The book is divided into two parts: Part one discusses the degrees of knowledge for science and philosophy - or 'rational knowledge,' and part two discusses the degrees of knowledge for religious faith and mysticism - or 'super-rational knowledge.'